Peran Pendidikan Jasmani Dalam Membentuk Budaya Kolaboratif Pada Era Kurikulum Merdeka - Ilham Kamaruddin; Taufiq Rahman; Nurfadillah; Friska Enytama El Husna; Eki Nurhikma; Haerul Ma'ruf (PT Mediatama Zayna Indonesia, 2026)
This study aims to analyze the role of physical education in fostering a collaborative culture in the Independent Curriculum era through a literature review approach. Six relevant articles were analyzed to examine how physical education learning contributes to strengthening collaborative values ​​and student character. Data analysis was conducted through article selection based on topic suitability, critical reading, thematic coding, and grouping findings into collaborative values ​​and character categories. The study results indicate that physical education plays a strategic role in fostering cooperation, communication, responsibility, and mutual cooperation values, which are part of the Pancasila Student Profile. Physical activity, traditional games, project-based learning, and fitness programs based on local wisdom have proven effective in strengthening students' social interactions. Although the implementation of the Independent Curriculum still faces challenges, such as limited facilities and teacher understanding, various learning innovations and collaborative support between schools, parents, and the community have shown a positive impact on fostering a collaborative culture. Furthermore, the integration of Pancasila values ​​into the physical education curriculum significantly contributes to increasing students' motivation, participation, and social skills. Overall, physical education is an important and potential space for building a collaborative, adaptive, and character-driven generation as required by the Independent Curriculum.